Effect of different levels from linseed oil and linseed oil beads on rumen fermentation and microbial parameters using gas production system and rumen simulation technique - Gawad, R.; Kattab, H.; Strabel, M.; Abo El-Nor, S.; Cieslak, A.; Zmora, P.; Elnashar, Magdy; El-Sayed, H.; Kolif, S. (Academic Journals Inc., 2015)
Despite the fact that the ruminant diet is rich in Polyunsaturated Fatty Acids (PUFA), ruminant products, such as meat, milk and dairy contain mainly Saturated Fatty Acids (SFA) because of bacterial lipolysis and subsequent biohydrogenation of ingested PUFA in the rumen. The link between SFA consumption and coronary heart disease is well established. The objectives of this study in this field were to find ways of manipulating ruminal microbes to increase the flow of PUFA from the rumen into meat and milk. The main objective of the current study was to evaluate new encapsulation method using biopolymers to protect linseed oil from rumen biohydrogenation and its effect on rumen fermentation and microbial parameters. Gas Production System (GPS) and rumen simulation technique (rustic system) were used in two separated experiments. Within GPS experiment, a mixture was used as a substrate which was comprised of meadow hay and barley meal in the ratio of 60:40. Linseed beads 1 (15% oil), linseed beads 2 (20% oil) and linseed oil were supplemented to the substrate at four levels (0, 2, 4 and 6%) from substrate as DM basis. The overall results from GPS trial concluded that beads 1, beads 2 and linseed oil in the free form at different levels did not have a negative effect on fermentation pattern in most cases. The only negative effect for linseed oil treatment was on protozoa count and it concluded that the encapsulation process has a good benefit to avoid this negative effect for linseed oil. The closed level for control case from these three treatments was 4% which was used for the next experiment. On the rustic system, the basal substrates consisted of grass hay and concentrate (corn meal+rapeseed meal) in a 1:1.5 ratio and were added in the portions of 12 g DM day-1. The treatments were as following: Control (Basel substrate without supplements), beads 1 (control+4% of linseedbeads containing 15% oil), beads 2 (control+4% of linseed beads containing 20% oil) and linseed oil (control+4% of linseed oil). Different fermentation parameters and microbial parameters were measured. The overall conclusion was that unprotected linseed oil had a significant negative effect on ammonia nitrogen andHolotricha protozoa. It also indicated that unprotected linseed oil had a negative effect on total bacteria count but not significant and no significant effect on other fermentation parameters. The results obtained using rustic system as a long term of incubation confirmed the results obtained by GPS as a short term of incubation. The results obtained conclude that unprotected linseed oil supplementation has a negative effect on rumen microflora, however, this negative effect could be avoided by protect linseed oil.